Research progress of mobile video prefetching for mobile content distribution networks - Shihang ZHANG; Yawen LUO; Min ZHANG; Qifu SUN; Xiaolong YANG (Dianxin kexue)
With the development of mobile internet and the popularization of video applications, the mobile content distribution network (MCDN) emerged as the times require.Prefetching technology is one of the key technologies for content distribution.It predicts the user’s future requests and prefetches the predicted content to the network edge in advance, thereby reducing the data acquisition delay and improving the quality of experience (QoE).In order to elaborate on the development status of mobile video prefetching technology, the latest research results of mobile video prefetching technology were introduced from the perspectives of user’s mobile behavior perception, content attribute perception, and network resource perception.And finally its main advantages and disadvantages were analyzed and the direction of further research in the future was pointed out.